Enzyme-assisted extraction of anti-inflammatory compounds from habanero chili pepper (Capsicum chinense) seeds - Cortes-Ferre, Hector Emmanuel; Antunes-Ricardo, Marilena; Gutiérrez-Uribe, Janet Alejandra (Frontiers in Nutrition, 2022)
Capsaicinoids are the main bioactive compounds extracted from chili pepper seeds (CPS) but other bioactive compounds such as phenolic compounds may be found. Enzyme Assisted Extraction (EAE) improves the extraction of bioactive compounds from fruits and seeds. The aim of this study was to establish the cellulase assisted extraction conditions of capsaicinoids and phenolic compounds from Habanero chili pepper (Capsicum chinense) seeds and to evaluate the anti-inflammatory activity of the obtained extracts on murine macrophages. EAE were performed using different temperature (T1= 30ºC, T2= 45ºC and T3= 60ºC), enzyme concentration (E1= 2500 UI/L and E2= 250 UI/L), and extraction time (0-150 minutes). Total phenolic compounds were quantified using Folin-Ciocalteau assay, capsaicin and dihydrocapsaicin content was evaluated by HPLC, and anti-inflammatory activity was performed with Griess assay on murine macrophage RAW 264.7 cell culture. The highest phenolic compounds content (337.96 mg GAE/L) was achieved at 30ºC, 2500 UI/L and 150 minutes of extraction. The highest capsaicin [CAP] content (310.23 g/mL) was obtained at 45ºC with 250 UI/L for 150 minutes, while for dihydrocapsaicin [DHC] (167.72 g/mL) the conditions were 60ºC, 2500 UI/L and 120 minutes. The highest anti-inflammatory response was obtained when 60ºC, E2 and 150 minutes were used for the extraction, NO production was reduced to 22.56%. Based on the results obtained in this research, EAE allowed the recovery of compounds with anti-inflammatory activity from CPS using water as solvent. There was a correlation between the extraction of CAP and DHC. But although a moderate direct correlation between the concentration of capsaicinoids and TPC, and an inverse correlation of the presence of the bioactive compounds (TPC, CAP and DHC) with the NO synthesis, these were not statistically significant. We demonstrated that Habanero seeds are an important raw material to recover anti-inflammatory compounds beyond capsaicinoids using water in EAE.